Circular RNA circBbs9 promotes PM2.5-induced lung inflammation in mice via NLRP3 inflammasome activation. (October 2020) - Li, Meizhen; Hua, Qiuhan; Shao, Yueting; Zeng, Huixian; Liu, Yufei; Diao, Qinqin; Zhang, Han; Qiu, Miaoyun; Zhu, Jialu; Li, Xun; Ling, Yihui; Zhang, Rong; et al.
Highlights: PM2.5 induces inflammatory response by NLRP3 inflammasome activation. CircBbs9 contributes to the pulmonary inflammation and thus further aggravates COPD caused by PM2.5 . CircBbs9 interacts with miR-30e-5p to facilitate the inflammation via activating NLRP3 inflammasome. Abstract: Fine particulate matter (PM2.5 ) is one of the most important components of environmental pollutants, and is associated with pulmonary injury. However, the biological mechanisms of pulmonary damage caused by PM2.5 are poorly defined, especially the molecular pathways related to inflammation. Following system exposure to PM2.5 for 3 months in normal mice and in chronic obstructive pulmonary disease (COPD) model mice, it was found that PM2.5 exposure increased the expression of IL-1β and IL-18 in lung tissues via NLRP3 activation, and these effects were more intense in COPD model mice. Circular RNA (circRNA) sequencing showed that the expression profiles of circRNAs were changed after PM2.5 exposure, and the positive roles of circBbs9 in inflammation induced by PM2.5 were verified. The circBbs9 knockdown alleviated PM2.5 -induced inflammation via NLRP3 inflammasome inactivation, as well as IL-1β and IL-18 inhibition in RAW264.7 cells, while overexpression of circBbs9 had the opposite effect. Bioinformatics and luciferase reporter assays showed that circBbs9 bound to microRNA-30e-5p (miR-30e-5p) and co-regulated the expression of Adar, a downstream target gene of miR-30e-5p. Taken together, these results revealed that PM2.5 induced pulmonary inflammation through NLRP3 inflammasome activation regulated by the circBbs9-miR-30e-5p-Adar pathway. Our findings provide a new target, circBbs9, for the assessment of lung inflammation and COPD exacerbation induced by PM2.5 exposure.